Odpowiedzi

Najlepsza Odpowiedź!
2010-02-04T12:59:54+01:00
3x³ + 6x² - 9x - 18 = 0
3x²(x+2) - 9(x+2) = 0
(3x² - 9) (x + 2) = 0
3x² - 9 = 0 x + 2 = 0
3x² = 9 /:3 x = -2
x² = 3 /√
x=√3 x=-√3
2010-02-04T13:02:59+01:00
3x³+6x²-9x-18=0
3x²(x+2)-9(x+2)=0
(3x²-9)(x+2)=0
3(x²-3)(x+2)=0
(x²-3)(x+2)=0
(x-√3)(x+√3)(x+2)=0

Równanie jest spełnione, jeśli dowolny czynnik jest zerem, czyli:
x₁=√3
x₂=-√3
x₃=-2
2010-02-04T15:13:10+01:00
3x³+6x²-9x-18=0 /:3
x³+2x²-3x-6=0
x²(x+2)-3(x+2)=0
(x²-3)*(x+2)=0
x²-3=0 v x+2=0
x=√-3 x=√3 x=-2